10 GHz Microstrip Spanar Antennas: An Experimental Analysis - Othman, Mohd Azlishah; Azman, Hazwani; Husain, Mohd Nor; Abd. Aziz, Mohamad Zoinol Abidin; Abd Rahim, Yahaya; Che Pee @ Che Hanapi, Ahmad Naim; Motsidi, Mohamad Radzi; Othman, Mohd Fairuz Iskandar (IOP Publishing, 2014)
This paper presents Spanar Antenna designed using CST Microwave Studio Simulation 2011. The proposed antenna was designed to operate at 10 GHz, which suggested return loss, S11 must be less than -10 dB and voltage standing wave ratio (VSWR) must be less than 2. The best performance of simulation of Spanar Antenna was obtained at a small size of 24.8 mm × 8.0 mm with dimension board of FR4 substrate 31.7 mm × 18.5 mm. The thickness (h) and dielectric constant (εr) of substrate were 1.6 mm and 4.7. An analysis between simulation result and measurement result has been compared in order to see the antenna performance.